A rare case of type III popliteal artery entrapment syndrome causing popliteal pseudoaneurysm - Jinshou Yang; Peng Liu; Yingxin Xu; Yan You; Xiao Di; Yuexin Chen (Heliyon)
Here, we report the case of a 30-year-old male who presented with acute right calf muscle pain. Computed tomography angiography revealed a popliteal artery aneurysm in the midsection. Popliteal fossa muscle tissue evaluation revealed that the popliteal artery aneurysm was located beneath an anomalous muscle bundle. Thus, the patient was diagnosed with type III popliteal artery entrapment syndrome and treated surgically. The patient was asymptomatic at rest and during physical activity 4 months after surgery with unobstructed bloodstream in the right popliteal artery. Popliteal artery entrapment syndrome should be considered in young male patients with popliteal artery pseudoaneurysms without atherosclerosis, hereditary diseases, or infections and treated surgically.